A Simple Theory of Industry Location and Residence Choice - Borck, Rainald; Pflüger, Michael; Wrede, Matthias (Journal of Economic Geography, 2010)
Trade and factor mobility allow for a separation of the location of production from the location of residences. We provide a simple general equilibrium model which endogenously determines these two choices. Our specific focus is on how residences and the locations of production are affected by the secular decline in trade and mobility costs that we witness. The main prediction of our analysis is that economic integration in the sense of a joint reduction of distance-related frictions eventually leads to an increased spatial concentration of production and a decreased concentration of residences. Intuitively, if distance-related costs fall, households' residence choices will be affected more strongly by the motive to avoid rising land rent, whilst the increasing strength of agglomeration economies induces a stronger concentration of production. We focus on and formalize the theory in terms of long-distance commuting. © The Author (2009). Published by Oxford University Press. All rights reserved.
WiSo-Import:2015-03-26:1062
Keywords: agglomeration; labour mobility; industry location; commuting